A Study on English Idioms Denoting Time with Reference to Vietnamese Equivalents - Vũ, Phương Thảo (Phenikaa University, 2024)
The reliable results of the research is the product of a process of detailed statistics and synthesis by the author with comparing, contrasting and relating reference documents. 102 idioms denoting time in English and 111 equivalents in Vietnamese have been compiled. The research is not only academically significant but also offers practical and cultural values. It helps readers and learners gain a more comprehensive and profound understanding of the richness and diversity of language and culture of the both countries. The graduation paper is a useful reference for English teachers and learners.